The role of age, experience, and physical fitness in technical performance in karate: An observational analysis - The role of age, experience, and physical fitness in technical The role of age, experience, and physical fitness in technical performance in karate: An observational analysis performance in karate: An observational analysis; Joaquim FERREIRA; Georgian BADICU; Jarosław MURACKI; Beata POŻAROWSZCZYK-KUCZKO; Adam KAWCZYŃSKI (Baltic Journal of Health and Physical Activity, 2025)
Background: This study aimed to investigate the relationships between age, experience, anthropometric measures, physical fitness, and the quality of technical performance in karate practitioners. We conducted an observational cross-sectional study with 53 federated karate athletes, aged 5 to 55, affiliated with the Youth Karate Association Portugal. The participants were divided into age and experience groups to assess differences in anthropometric measures (body mass, height, BMI) and physical fitness (strength, power, flexibility). The technical performance of four specific karate techniques – kizami, gyaku zuki, mawashi geri, and ura mawashi geri – was evaluated using a custom-designed technical evaluation system. Descriptive statistics and inferential analyses, including one-way ANOVA, Kruskal-Wallis tests, and Mann-Whitney U tests, revealed significant differences in physical fitness and technical performance across age groups and years of experience (p < 0.05). Younger practitioners demonstrated lower performance in strength, power, and technical execution, with those over 19 exhibiting the highest levels. Specifically, significant differences were observed in body mass (F = 57.866, p < 0.001, η² = 0.780), IMTP (F = 25.229, p < 0.001, η² = 0.660), CMJ (F = 7.279, p < 0.001, η² = 0.308), and grip strength (F = 40.513, p < 0.001, η² = 0.713). Significant correlations were found between physical f itness measures (e.g., strength, power) and the quality of technical execution (p < 0.05), highlighting the dependency of technical proficiency on physical attributes such as muscle strength and explosive power. Spearman's Rho test identified significant moderate to large correlations between years of experience and technical execution quality in kizami (rho = 0.388, p = 0.004), gyaku (rho = 0.436, p = 0.001), mawashi geri (rho = 0.603, p < 0.001), and ura mawashi geri (rho = 0.477, p < 0.001). These findings suggest that experience is critical in improving karate performance, with experienced athletes demonstrating superior technical skills and physical fitness compared to beginners. This study underscores the importance of incorporating both physical conditioning and skill-specific training to optimize performance in karate and provides insights for coaches to tailor training programs according to an athlete’s age and experience level. Future research should explore the long-term effects of training on the development of both physical and technical capacities in martial arts.